2013
DOI: 10.1155/2013/852472
|View full text |Cite
|
Sign up to set email alerts
|

Data Dissemination in Mobile Wireless Sensor Network Using Trajectory-Based Network Coding

Abstract: With GPS devices spreading, more mobile nodes are guided by the navigation systems to select better paths. The performance of mobile networks can be improved with the navigation information in nodes. In this paper, we propose a trajectory-based network coding (TBNC) method to disseminate data in mobile wireless sensor network (MWSN). It is designed according to the characteristics of MWSN and is appropriate for the mobile nodes that share anonymously its GPS pretrajectory for the higher bandwidth. Data are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this section, we generate the mobile nodes on the ONE simulator (The ONE) and evaluate the performance of our NC/CTE method in contrast with Epidemic (Vahdat and Becker, 2000), PRoPHET (Lindgren et al, 2003), TBNC (Li et al, 2013) and generic Wi-Fi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we generate the mobile nodes on the ONE simulator (The ONE) and evaluate the performance of our NC/CTE method in contrast with Epidemic (Vahdat and Becker, 2000), PRoPHET (Lindgren et al, 2003), TBNC (Li et al, 2013) and generic Wi-Fi.…”
Section: Discussionmentioning
confidence: 99%
“…In our former work (Li et al, 2013), the trajectories of mobile nodes are computed in a central manager server. As the number of nodes or the speed of the nodes increase, the processing time in the server will get longer, and the trajectory estimation will not be accurate because the result of the calculation is late in contrast to the movement of nodes.…”
Section: Using Trajectory Estimation In Network Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al [14] showed the advantage of the proposed XORs coding scheme over the traditional wireless broadcast in the bandwidth efficiency through simulation and theoretical analysis. Network coding is also used in mobile wireless sensor network [15] to adapt for the dynamics velocity of mobile nodes. However, all the above algorithms cannot be used in wireless sensor network, because they did not consider sleep scheduling.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, Francesca Cuomo propose a high throughput dissemination scheme for VANET based on the dynamic formation of a multi-hop backbone network in [6], he describe and analyze such a networking protocol when used to broadcast message flows generated by a Road Side Unit along a linear road, forming a VANET structure that is identified as a Vehicular Backbone Network (VBN). In [7], Lingzhi Li present a trajectorybased network coding (TBNC) method to disseminate data in Mobile Wireless sensor network (MWSN), and the experiments show that TBNC is able to reduce overhead messages, and enhance the reliability of transmission.…”
mentioning
confidence: 99%